2011
DOI: 10.1007/s00040-011-0192-8
|View full text |Cite
|
Sign up to set email alerts
|

Ants use pheromone markings in emigrations to move closer to food-rich areas

Abstract: Nest site quality can affect survival and reproduction, and thus many animals have evolved behaviors which facilitate nest site assessment and selection. Ants of the genus Temnothorax have been shown to include an array of nest site attributes when choosing such a site. Here, we show that they also include traits of the habitat surrounding nest sites. In particular, we found that during emigration, ants preferred to move to nests located close to a previously explored food-rich area. We also determined that sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Stroeymeyt et al [41] showed that house hunting Temnothorax ants relied on prior experience (navigational memory) when chemical markings in their laboratory arena were experimentally reversed. This suggests a preference for private information over social information, though ants of this genus rely on tandem-running for recruitment during consensus decision making [48] and the role of chemical markings differs to that in Myrmecina [33]. Maintenance of some degree of independence in collective decisions such as this is perhaps not surprising as an individual component to choice is thought to be integral to an effective quorum response [32], and this vetting process may also buffer colonies against negative information cascades [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stroeymeyt et al [41] showed that house hunting Temnothorax ants relied on prior experience (navigational memory) when chemical markings in their laboratory arena were experimentally reversed. This suggests a preference for private information over social information, though ants of this genus rely on tandem-running for recruitment during consensus decision making [48] and the role of chemical markings differs to that in Myrmecina [33]. Maintenance of some degree of independence in collective decisions such as this is perhaps not surprising as an individual component to choice is thought to be integral to an effective quorum response [32], and this vetting process may also buffer colonies against negative information cascades [8].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other social insects so far studied (though see [33]), the small-colony ant Myrmecina nipponica relies on pheromone trails to navigate during house hunting [34]. Trails are laid by scouts that have found a suitable new nest site, leading to the recruitment of other nest-mate scouts and, once an apparently quorum-based threshold is reached, a switch to brood transport [34].…”
Section: Introductionmentioning
confidence: 99%
“…The small size of the colonies and the locations of their nests (in cracked or flaking rocks) allow for easy collection of the entire colony, including queen and brood. The tolerance of many species in the Temnothorax genus for laboratory conditions allows for empirical studies in controlled conditions, resulting in this genus being used successfully used in behavioral studies in many contexts, meaning well-established methods for empirical studies exist (e.g., emigrations (Cao and Dornhaus 2012), group decision making (Sasaki and Pratt 2013), and intracolony interactions (Dornhaus et al 2008(Dornhaus et al , 2009). …”
Section: Model Speciesmentioning
confidence: 99%
“…The quality of nests chosen varies, at least in part, because many factors can influence nest choice. These factors include differences among individuals in decision criteria (29,98,114) and the effects of current conditions such as where ants have previously found food (16), the location of the queen (28), recent foraging locations (120), and frequency of disturbance (89). The second line of evidence is that emigration is easily initiated and difficult to stop, favoring moving somewhere over not moving at all.…”
Section: Nest Emigrationmentioning
confidence: 99%